Novos paradigmas: pontes entre o mal-estar e o bem-estar docente = New paradigms: bridges between discomfort and wellbeing of teachers - Ruth Catarina Cerqueira Ribeiro de Souza (Universidade de Brasília, 2012)
Este artigo propõe uma análise sobre processos de formação docente em relação com trajetórias de professores de escolas públicas e processos de emancipação. Apresenta uma reflexão sobre a lógica do ambiente escolar, o distanciamento e o envolvimento entre professores e alunos. Traz uma discussão sobre identidade profissional docente, profissionalização e participação em sindicatos e associações. Analisa a fragilidade associativa, discute a desvalorização docente nos documentos oficiais e na mídia como geradoras do mal-estar docente e as pontes para o bem-estar a partir das relações formação e emancipação.This article proposes an analysis of teacher training processes in their relationship with the course of the work life of public school teachers, and with processes of emancipation. It presents a reflection on the logic of the school environment, estrangement and involvement between teachers and students. It brings forth a discussion about teachers' professional identity, professionalization and participation in labor unions and associations. It analyses the fragility of associations, discusses the belittling of teachers in official documents and the media, as factors generating discomfort among teachers, and the bridges towards wellbeing, based on educational and emancipatory relationships.